Narratives of melancholy: a humanities approach to depression. - Flynn, Deborah (Medical humanities, 2010)
This paper explores narrative literature as a means of inquiry into the sense of self in depression. Described as a disease, an identity and a way of life, depression is influenced by both internal and external factors. Although brain research has provided new insight into the relationship between neurotransmitter function and depression, the symptoms are experienced by individuals whose lives are intertwined with historical and sociocultural interpretations of illness and its manifestations. At the intersection of science and the humanities, narratives aid in the interpretation of lived experiences, provide a window to that experience, and a public medium that engages writers and readers as they interpret the world. Engaging narratives to interpret both experience and medical jargon may reveal for both those experiencing depression and those engaged in their care, a way of mediating that experience. Narratives can help dissect and thus illuminate the official language of medicine and psychiatry and the personal language of depression. Such a window can enhance the opportunities for empathy and care.
Keywords: *Depressive Disorder/hi [History]; *Humanities; *Narration; Depression; Depression/hi [History]; Depressive Disorder; Female; History, 18th Century; History, 19th Century; History, 20th Century; Humanities; Humans; Literature and medicine; Male; Narration; Self Concept; article; depression; dept.pch; female; history; human; humanities; male; narrative medicine; patient narrative; psychiatry; self concept; verbal communication

Patterns in office referral data by grade, Race/Ethnicity, and gender - Kaufman, Joy S.; Jaser, Sarah S.; Vaughan, Ellen L.; Reynolds, Jesse S.; Di Donato, John; Bernard, Stanley N.; Hernandez-Brereton, Maria (Journal of Positive Behavior Interventions, 2010)
Research supports that office referral data is useful in informing programmatic decisions and planning interventions such as Positive Behavior Supports (PBS). Knowledge of patterns of office referrals may facilitate development of interventions that target specific groups. This study examines patterns in office referrals within an urban district by gender, race/ ethnicity and grade. Findings reveal that there are differences by grade that appear to be related to developmental level, with more referrals for aggression in younger students (grades K-6), disrespectful behavior in middle school students (grades 7-8), and attendance problems in high school students. Gender differences in the rate and type of referrals were found, with significantly more referrals for boys' delinquent/aggressive behavior, which may relate to how schools define unacceptable behavior and the data collection method. Finally, there were significantly more referrals for African American/black students than Hispanic students, suggesting that schools consider racial differences when developing behavioral expectations.
Keywords: Office referral data; Positive behavioral supports; Schools; dept.pch

Trends in alcohol consumption among undergraduate students at a northeastern public university, 2002-2008. - Bulmer, Sandra Minor; Irfan, Syed; Mugno, Raymond; Barton, Barbara; Ackerman, Louise (Journal of American college health : J of ACH, 2010)
OBJECTIVE: This study examined alcohol consumption patterns and trends at a public university in the Northeast from 2002 to 2008., PARTICIPANTS: Stratified random sampling was used to select undergraduate students enrolled in courses during spring semesters in 2002, 2004, 2006, and 2008., METHODS: Data were collected during regularly scheduled classes for 4 measures of alcohol consumption and 5 demographic categories using the Core Alcohol and Drug Survey., RESULTS: Four groups showed significant increases in both frequency and volume of alcohol consumption-students who were female, over 21 years of age or over, living off-campus, or performing well academically. There were no decreasing trends for any demographic group. These results differ from national college health surveys, which have shown alcohol use remaining steady during this period., CONCLUSIONS: Campus-specific trend data can provide unique perspectives and guide programming efforts. These trends suggest a need for new intervention strategies on this campus.
Keywords: *Alcohol Drinking/ep [Epidemiology]; *Public Sector/sn [Statistics & Numerical Data]; *Students/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Alcohol Drinking; Alcohol consumption; College; Connecticut; Data Collection; Drinking; Female; Humans; Male; Public Sector; Risk-Taking; Statistics, Nonparametric; Students; Trends; United States; Universities; Young Adult; adult; article; dept.mat; dept.pch; drinking behavior; female; high risk behavior; human; information processing; male; nonparametric test; organization and management; peer-reviewed; statistics; student; university